Genetic association studies, TDT and the candidate gene approach - Knight, Jo (Henry Stewart Talks, 2007)
Background of genetic studies, Structure of a gene, Simple association, Linkage disequilibrium and haplotypes, Multi-marker association, Family-based association, Practicalities of programs and power